An acoustic study on character voices of dominators and subordinates: A case study on male characters in Empresses in the Palace - Liu, Wen; Zhang, Xinyi; Liang, Changwei (Frontiers in Communication, 2023)
Introduction Voice has been used to project identity in dubbing, in order to auditory portray appropriate role images in TV dramas. This study investigates the character voices of leading male characters in Empresses in the Palace. Methods Different acoustic characteristics of character voices and matching relation between acoustics and role images are explored by comparing F0, CPP, harmonic amplitude differences of speech spectrum. Results The voice quality of characters is related to their relative social status. The subordinates usually adopt a higher pitch or breathy voice, while the dominators use a lower pitch or modal/creaky voice. In addition, CPP, F0, and H1-A3 are the key acoustic indicators to distinguish character voices. Discussion These results reveal the acoustic characteristics of character voices of certain types, as well as provide guidance for dubbing vividly.